Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menggunakan Metode Profile Matching Pada Alia Citra Dekorasi (ACD) - Selvia Septi Palupi; Satia Suhada (Jurnal Larik: Ladang Artikel Ilmu Komputer, 2021)
Employees are one of the main things in a company both in the progress, smoothness, and success of a company, the role of employees is very important. The company realizes how important the role of employees is in the success of a company, therefore the company tries to continue to provide motivation, one of which is by selecting the best employees. The selection of the best employees at Alia Citra Decor (ACD) is still done manually, namely selecting employees who are considered to have good performance by company leaders without an accurate assessment. To overcome these problems a decision support system (SPK) with the Profile Matching method is very helpful in solving the problem of selecting the best employees at Alia Citra Decor. By using the Profile Matching method, ACD can make decisions through employee performance appraisals based on existing aspects according to abilities. With the Profile Matching method, it is possible to determine the percentage of objects or aspects that are assessed and totaled, then a ranking process is carried out which will determine the optimal alternative, namely the best employees.